PENGARUH LAYANAN ORIENTASI TERHADAP KEMANDIRIAN BELAJAR KELAS X SMAIT AL-FITYAN KABUPATEN KUBU RAYA - Syaputra, Rendy Zulfian Ade; Asrori, M.; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractOrientation service is a service provided to students both new and old as well as other parties to know and understand the circumstances and situations that exist in the school environment both the learning environment and the social environment in general so that students can easily realize their current condition The problems in this study are (1) How is the orientation service for students in class X of Al-Fityan Integrated Islamic High School in Kubu Raya Regency? the influence of service orientation towards the kemadirian learning class X Al-Fityan Integrated Islamic High School in Kubu Raya Regency? The method used is descriptive method and the form of research is a form of influence study studies. The population in this study were 62 students of class X Al-Fityan Integrated Islamic High School, Kubu Raya Regency. Based on research results, the influence is very significant, reaching 79% service orientation towards learning independence. Then it can be concluded that the better the orientation services provided by the BK teacher, the better the student's learning independence.Â Keywords: Orientation Services, Learning Independence